SELF ASSESMENT SYSTEM, TRANSFER PRICING, TAX AVOIDANCE, GOOD CORPORATE GOVERNANCE TERHADAP KETIDAKPASTIAN LINGKUNGAN DENGAN KESADARAN WAJIB PAJAK SEBAGAI VARIABEL MODERATING - Arief Fadilah; Karsam (Universitas La Tansa Mashiro, 2026)
Understanding the self-assessment system, transfer pricing, tax avoidance, and good corporate governance in relation to environmental uncertainty, with taxpayer awareness as a moderating variable. The research sample consisted of 200 respondents, comprising 10 respondents from the hospitality industry and 190 respondents from MSMEs, analyzed using the Smartpls statistical t-test software. The results showed that taxpayer awareness can mediate the self-assessment system, tax avoidance, and good corporate governance in relation to environmental uncertainty. Meanwhile, taxpayer awareness cannot mediate transfer pricing in relation to environmental uncertainty.